A SEQUENCE OF FORMATION OF «URANPYROCHLORE» AND FLUOROCALCIOPYROCHLORE IN ALKALI PEGMATITES FROM THE VISHNEVYE MOUNTAINS, SOUTH URALS - V.I. Popova; V.A. Popov; I.A. Blinov; V.A. Kotlyarov; S.M. Lebedeva (Минералогия)
The sequence of formation of pyrochlore crystals of various morphology and composition is considered in an aggregate with ilmenite and feldspar from nepheline-feldspar pegmatite at Mt. Dolgaya (Vishnevye Mountains, South Urals): altered yellowish green «uranium pyrochlore» with a UO3 content of 7.62–42.44 wt. % in different parts of the crystal, as well as fluorocalciopyrochlore, fersmite, and associated minerals. The alteration of «uranpyrochlore» includes fersmitization and silicification in contrast to relatively late fluorocalciopyrochlore and fersmite. The compositions and Raman spectra of altered «uranpyrochlore» and later fluorocalciopyrochlore are given.